Tata Ruang Dan Penilaian Dampak Lingkungan Industri Di Bangkalan Pasca Pembangunan Jembatan Suramadu Berdasarkan Potensi Daerah - Utami, Issa Dyah; Findiastuti, Weny; Kuswanto, Dwi; Singgih, Moses L. (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
The development of Suramadu Bridge that connects Java Island and Madura Island opens the opportunity for Bangkalan Regency to be one of Industrial Park at East Java Province.Â This could be realized if there are many investors who invest their capital and build their industry at the industrial Park. The Clustering analysis and Scoring Risk analysis are used in this research. The results of this study indicate that based on the industrial potential, Bangkalan region is divided into six regions. Region I is the most appropriate area to serveÂ industrial and commercial center. The study also build a StandardizedÂ Information System as a guide for the investors to invest their capital. This contains information about Industry Spatial Planning and Clustering based on area potency of bangkalan Regency and Environmental Impact.